2010
DOI: 10.1186/1746-160x-6-17
|View full text |Cite
|
Sign up to set email alerts
|

Release kinetics of VEGF165 from a collagen matrix and structural matrix changes in a circulation model

Abstract: BackgroundCurrent approaches in bone regeneration combine osteoconductive scaffolds with bioactive cytokines like BMP or VEGF. The idea of our in-vitro trial was to apply VEGF165 in gradient concentrations to an equine collagen carrier and to study pharmacological and morphological characteristics of the complex in a circulation model.MethodsRelease kinetics of VEGF165 complexed in different quantities in a collagen matrix were determined in a circulation model by quantifying protein concentration with ELISA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…composites with biomaterials and others) and conditions like application mode including activation and indication of PRP formulations to get a more precise impression of the individual kinetics of growth factors in a PRP setting. Thus, for example Kleinheinz and colleagues found an enhancement of VEGF 165 (vascular endothelial growth factor) half-life from 90 min for free VEGF 165 up to 48 h when embedded into a collagen matrix [20]. Presuming different half-life data of growth factors in dependence on the respective preparation and setting it seems to be essential to estimate cytokine stability over time not only for the main classifications of liquid platelet-rich products (P-PRP, L-PRP) but also for each individual preparation protocol currently in use.…”
Section: Discussionmentioning
confidence: 99%
“…composites with biomaterials and others) and conditions like application mode including activation and indication of PRP formulations to get a more precise impression of the individual kinetics of growth factors in a PRP setting. Thus, for example Kleinheinz and colleagues found an enhancement of VEGF 165 (vascular endothelial growth factor) half-life from 90 min for free VEGF 165 up to 48 h when embedded into a collagen matrix [20]. Presuming different half-life data of growth factors in dependence on the respective preparation and setting it seems to be essential to estimate cytokine stability over time not only for the main classifications of liquid platelet-rich products (P-PRP, L-PRP) but also for each individual preparation protocol currently in use.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin can release and disperse FGF2 and FGF10, enabling activation of cells at a distance and altering gradients (99, 100). Similarly, VEGF release by proteases and heparanases produces diffusible VEGF that can escape subsequent rebinding to the matrix and is resistant to degradation (13, 101). Carriers may also enhance the spatial complexity of the local VEGF gradients (21, 102).…”
Section: Local Availability and Activity Of Vegf: Ecm Proteases Amentioning
confidence: 99%
“…12,26 The effect of this local application was insufficient for fracture healing in segmental defect models. Recently, Kleinheinz et al 16,27 demonstrated a linear declining gradient in release kinetics of a VEGF-soaked collagen I carrier. On the basis of this in vitro release kinetics of different concentrations of rhVEGF 165 , the calculated half-life, and known concentrations required for semi-maximal biologic activity of rhVEGF 165 (ED 50 ¼ 2-6 ng/ml) for activating endothelial cells, we assessed the optimal concentration of rhVEGF 165 per implant (12 mg).…”
Section: Discussionmentioning
confidence: 98%